Pengaruh Opini Audit Tahun Sebelumnya Dan Kualitas Audit Terhadap Penerimaan Opini Audit Going Concern (Studi Empiris pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di BEI Tahun 2012-2016) - Ariasna, Ketut; Apriliani, Binari (Fakultas Ekonomi Universitas Gresik, 2019)
The research aims to examines and proves the influence ofÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â prior opinion and audit quality would receive a going concern opinion. The sample selection has been done by using purposive sampling method on Property and Real Estate companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2016 periods. Based on the sample research method, 185 companies have been obtained as samples. The data analysis of this research has been carried out by using logistic regressions and the statistic test instrument SPSS 22rd version. The results of this research is that the prior opinion are positive significantly affect the going concern audit opinion. On the other hand, audit quality does not have effect on going concern audit opinion.keywords : going concern, audit opinion, audit qualityDOI : 10.5281/zenodo.3474549